Pemanfaatan Limbah Bulu Ayam Dan Kulit Kacang Tanah Sebagai Bahan Pembuatan Kertas Seni Dengan Penambahan Cao Dan Pewarna Alami - Rahmawati, Suci Siska; , Dra. Aminah Asngad, M.Si (2015)
Quill and Peanut Leather is a basic ingredient in the manufacture of art paper because quill it contains fiber and peanut leather contain cellulose and lingnin. Teak leaves containing anthocyanins and papaya leaves contain chlorophyll which is either used for natural dye art paper. Research paper aims to determine test tensile strength, tear strength and sensory test art paper with raw sewage and quill, peanut leather waste with the addition of CaO and natural dyes. This study used an experimental method with a completely randomized design (CRD) with two treatment factors: factor 1: comparison of the composition of (A), A1: 50% of quill : 50% peanut leather, A2: 40% of quill : 60% paeanut leather, A3: 30% of quill: 70% peanut leather. Factor 2: The dye (B), B1 (no color), B2 (teak leaves), B3 (papaya leaves) each treatment was performed 2 times repetition. Data collection techniques in this research is descriptive qualitative. The conclusions of this research there is a difference between tensile strength and tear strength is influenced by differences in composition.